Current state of smart city concept - Baptista, Aldair (2025)
The concept of smart cities has undergone significant evolution over the past two decades, representing a global paradigm shift in urban development. Defined as an integration of physical infrastructure and information and communication technologies, smart cities aim to enhance municipal services, ensure socioeconomic sustainability, and promote economic well-being. This development presents a pluralized meaning, with regions prioritizing either technology-driven or sustainable development models. European countries, particularly Germany (e.g., Berlin, Munich, Hamburg), are leading in smart city adoption by integrating digital technologies, IoT, and AI for sustainable urban solutions, emphasizing a balance between technology and societal/environmental strategies. Despite their long-standing conceptual development and promises of improved quality of life, sustainability, and operational efficiency, current smart city initiatives face scrutiny regarding tangible outcomes. Academic literature reveals persistent gaps, including a lack of unified theoretical frameworks, neglect of marginalized populations, potential environmental risks from technological advancements, limited empirical validation, and a tendency for smart cities to operate in silos, disconnected from broader policy frameworks. Addressing these challenges is crucial for the continued evolution and effective implementation of smart city initiatives.